2020
DOI: 10.1088/1361-6528/ab9da5
|View full text |Cite
|
Sign up to set email alerts
|

Selective antifungal and antibacterial activities of Ag-Cu and Cu-Ag core–shell nanostructures synthesizedin-situPVA

Abstract: A simple chemical reduction method was employed to synthesize Cu-Ag and Ag-Cu core-shell nanostructures inside polyvinyl alcohol (PVA) matrix at room temperature. The core-shell nanostructures have been synthesized by varying the two different concentrations (i.e. 0.1 and 0.01 M) of the respective metal ions in equimolar ratios using successive reduction with hydrazine hydrate (HH) as a reducing agent. The core-shell nanostructures have been further characterized by different characterization techniques. The U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 54 publications
1
9
0
1
Order By: Relevance
“…Similar conclusions was obtained in another study, which indicated that Ag and Cu NPs, in a core-shell microstructure, had excellent antimicrobial activities against both Gram-positive and Gram-negative bacteria, especially when the Ag:Cu ratio was 0.4 [246]. However, in the case of antifungal properties, Ag core Cu shell nanoalloys were found not to demonstrate higher activity than single Ag NPs [231]. Another viewpoint holds that Ag shell Ag-Cu core nanoalloys have long-term antimicrobial activity because the Ag shell has excellent oxidative stability [232].…”
Section: Antimicrobial Potential Of Mixed Ag-cu Nps and Agcu Nanoalloyssupporting
confidence: 86%
See 1 more Smart Citation
“…Similar conclusions was obtained in another study, which indicated that Ag and Cu NPs, in a core-shell microstructure, had excellent antimicrobial activities against both Gram-positive and Gram-negative bacteria, especially when the Ag:Cu ratio was 0.4 [246]. However, in the case of antifungal properties, Ag core Cu shell nanoalloys were found not to demonstrate higher activity than single Ag NPs [231]. Another viewpoint holds that Ag shell Ag-Cu core nanoalloys have long-term antimicrobial activity because the Ag shell has excellent oxidative stability [232].…”
Section: Antimicrobial Potential Of Mixed Ag-cu Nps and Agcu Nanoalloyssupporting
confidence: 86%
“…Another study used oleyl amine as both reducing agent and surfactant, to synthesize nanoalloys from a solution of Ag and Cu(I) complexes, which gave a randomly distributed AgCu solid solution [230]. The chemical reduction method is also used to synthesize AgCu nanoalloys with the microstructure of either Ag core Cu shell or Cu core Ag shell , depending on the sequence of reduction reactions [231].…”
Section: Synthesis Of Agcu Nanoalloysmentioning
confidence: 99%
“…Additionally, the authors report that both FSNC and FGNC could enhance leakage of cellular components like proteins, reducing sugars, DNA and RNA. Sabira et al [100] tested the antifungal activity of two core-shell bimetallic nanoparticles (Cu-Ag and Ag-Cu) synthesized using polyvinyl alcohol (PVA) matrix. In this study, Cu-Ag core-shell NPs exhibited a better antifungal activity against A. fumigatus than Ag-Cu NPs, causing an inhibition zone of 23 and 16 mm, respectively, at 0.1 M. Contrarily, Ag-Cu showed a better fungicidal effect than Cu-Ag with minimum fungicidal concentration (MFC) of 15 and 25 µg/mL, respectively, also causing damage in fungal cell wall as observed by scanning electron microscope (SEM) images.…”
Section: Organic Materials-based Nanoparticlesmentioning
confidence: 99%
“…AgNPs Growth inhibition at 10 µg/mL [33] 54% growth inhibition at 100 mg/L [92] 75.61% growth inhibition at 150 µg/mL [105] Growth inhibition at 150 µg/mL [106] Growth inhibition at 40 µg/mL [107] 60% growth inhibition at 50 µg/mL [110] Marketed AgNPs 90% growth inhibition at 0.5 µg/mL (clinical isolates) [93] AgO/Ag NPs 75.25% growth inhibition at 50 µg/mL [113] Ag-AuNPs 90.78% growth inhibition at 200 µg/mL [111] Ag 2 Cr 2 O 4 3.1 times higher inhibition than fluconazole [94] Maleic acid capped AgNPs Growth inhibition [74] Milk protein synthesized AgNPs Growth inhibition [95] Fibroin-AgNPs Fungicidal activity at 2 µg/mL [99] Ag-Cu core-shell NPs Growth inhibition at 0.1 M and fungicidal activity at 15 µg/mL [100] CChG/AgNPs Better growth inhibition than AmB at 0.98 µg/mL [101] CuNPs Growth inhibition at 31.67 µg/mL [107] Cu-Ag core-shell NPs Growth inhibition at 0.1M and fungicidal activity at 25 µg/mL [100] Au@5FU NPs Higher inhibition than 5FU [96] Fibroin-AuNPs Fungicidal activity at 10 µg/mL [99] TiO 2 -PLA NPs 99.9% growth inhibition at 8 wt% of NPs [97] pMWCNT-CD/Ag-TiO 2 nanosponge Growth inhibition at 437.5 µg/mL [98] Table 3. Cont.…”
Section: Nanomaterials Antifungal Effect Referencementioning
confidence: 99%
“…Phổ hấp thụ của hạt Ag cho dải cộng hưởng plasmon bề mặt (SPR) với cường độ mạnh, từ 320 đến 500 nm với cực đại ở khoảng 405 nm[10], còn hạt nano Cu cho dải SPR rộng từ 450 đến 850 nm với đỉnh có cường độ yếu hơn ở bước sóng 570 nm.Trong khi đó, đối với vật liệu nano phức hợp Ag-Cu@CS, đỉnh hấp thụ plasmon cực đại (SPR) đã bị dịch chuyển sang bước sóng 415 nm, chứng tỏ có sự hình thành cấu trúc phức hợp giữa các hạt nano Ag và Cu. Sự tăng cường tính chất cộng hưởng plasmon bề mặt của các hạt phức hợp được giải thích dựa vào sự thay đổi tính chất điện tử bề mặt của các thành phần trong hệ vật liệu phức hợp[1].Hình 1: Phổ FTIR (a) và phổ UV-Vis của dung dịch nano phức hợp Ag-Cu@CS thu được (b) Hình 2: Ảnh hiển vi điện tử truyền qua TEM với độ phóng đại 100.000 lần (a); 200.000 lần (d) và giản đồ phân bố kích thước hạt (c) của dung dịch nano phức hợp Ag-Cu@CS https://doi.org/10.51316/jca.2021.085 28…”
unclassified